Implementación y configuración de la intranet en el laboratorio de investigación y de Ingeniería de Software de la Universidad Técnica de Cotopaxi "Extensión La Maná", año 2017 - García Ayala, Amparito Cecilia (2017)
The present project aims to implement an intranet that allows agile and timely communication in the research and software engineering laboratory of the Technical University of Cotopaxi, La Maná, due to the lack of an intranet model that allows an efficient fluidity of the information causing that the computer resources of the laboratory do not take advantage of optimal form. In view of the aforementioned problem arises the idea of implanting an intranet in the research laboratory that allows a database for an efficient management in the same. For this purpose it will be used the descriptive research that will allow to detail the current situation of the laboratory under study; in addition, it was suggested the application of documentary research for the collection of theoretical information. Also the field and experimental research will allow carrying out the surveys and implementing the proposal of the intranet. Among the methods to be used are the deductive to establish the problematization, background and scientific questions or hypotheses; through the analytical method, the analysis of the information obtained through the surveys and the direct observation will be carried out. The data collected will allow us to know the current situation and propose an alternative solution to the deficiencies detected in the use of data in the laboratory of the Technical University of Cotopaxi for which it will be necessary to choose the appropriate model of intranet that suits the activities performed in the laboratory considering their organization, number of departments and type of data stored. In addition, it should be considered who will be the administrator of the intranet and through it will collect information from the students to maintain an efficient monitoring and facilitate data in an agile and efficient manner. Therefore considering the above aspects the impact of the proposal will have a high technological impact because with the implementation of the intranet an information system would be applied to facilitate its processing, revision and updating.